The evolution of technical prerequisites and local boundary conditions for optimization of mitral valve interventions—Emphasis on skills development and institutional risk performance - Cocchieri, Riccardo; van de Wetering, Bertus; Baan, Jan; Driessen, Antoine; Riezebos, Robert; van Tuijl, Sjoerd; de Mol, Bas (Frontiers in Cardiovascular Medicine, 2023)
This report describes how the evolution of transcutaneous mitral valve intervention (TMVI ) is influenced by lessons learned from three evolutionary tracks: 1. the development of state of the art treatment from mitral valve surgery (MVS) to transcutaneous procedures; 2. the evolution of biomedical engineering for research and development resulting in predictable and safe clinical use; 3. the adaptation to local conditions, impact of transcutaneous aortic valve replacement (TAVR) experience and creation of infrastructure for skills development and risk management. Abundant literature regarding MVS experience shapes the indication area and treatment expectations for TMVI, including transcutaneous edge-to-edge repair (TEER) and transcutaneous mitral valve replacement (TMVR). The expected performance of TMVI should be measured by standards of risk-benefit considerations and actual outcomes set by minimally invasive mitral valve surgery (MIMVS). At the institutional level, heart teams can make decisions based on the best knowledge acquired from surgical experience in mitral valve disease. The evolution of TMVI evidently meets challenges due to the complexity of the mitral valve apparatus and is still limited to high-risk surgical cases. Indications and risk-benefits are still in development depending on the complexity of the device, including TMVR. Biomedical engineers describe the Research and Development cycle for TMVI, including the relevance of human factor engineering. In the R&D phase estimations of the strengths and limitations of clinical use should be made, including the level of skills and associated necessary training. This can be done by a Physicians Preference Test or use of a biosimulator. Supported by clinical data from two heart centers in Amsterdam, we additionally describe the evolution of a professional ecosystem for applying innovation. Adaptation to local conditions in terms of infrastructure, referrals and reimbursement appears essential for the evolution of a complete mitral valve disease management program. Efficacy of institutional risk management performance (IRMP) and sufficient team skills should be embedded in an appropriate infrastructure, which enables scale and offers complete and safe solutions for mitral valve disease. The longstanding evolution of mitral valve therapies is the result of working devices embedded in an ecosystem focused on developing skills and effective risk management actions.